Regional deformations and emplacement of granitoid plutons in the Hackett River greenstone belt, Slave Province, Northwest Territories - Fyson, W. K.; Frith, R. A. (Canadian Journal of Earth Sciences, 1979)
Regional foliations resulting from two main phases of deformation within the Archean Hackett River greenstone belt are generally steeply inclined, except near some granitoid plutons where one or both structures are shallow dipping. Inclinations decrease near the plutons with little deviation in regional strike. Near other plutons all structures are steep; in some cases steep second phase foliation passes into the granitoid rock. It is suggested that the shallow dips reflect modifications of regional strain induced solely by those plutons that were rising during the phases of regional deformation. From changes in the structural arrangement along the belt it can be inferred that plutons rose into higher grade metamorphic rocks earlier than into lower grade rocks.A domal structure in basal gneiss could have formed during a late stage of the second deformation. Shallow dipping foliation within the gneiss may, however, reflect not only strain modification during regional deformation and buoyant uplift, but also the initial configuration of an infrastructure.